If you love me when I’m breathing; you don’t love me when I’m dead? - Minkley, Emma (Kronos: Southern African Histories, 2024)
This article looks to the form of the puppet, both an oral and aural entity, as a receptacle or instrument which allows for a ventriloquism to take place in partnership with the puppeteer. In the work of South African Handspring Puppet Company, the puppet is a receptacle for sound, but also for the human body itself – a chamber within a chamber – highlighting the instrumentalisation of the body. In this regard, the article looks to Handspring’s I Love You When You’re Breathing, particularly in reference to a comment once made by an audience member at a performance of the show that I watched in relation to the title; ‘If you love me when I’m breathing; you don’t love me when I’m dead?’ In the practice of puppetry there is a focus on the ways the puppeteer conveys life in the puppet. Here, breath is significant as a sound, but more so as a movement, passed from puppeteer to puppet, a kind of bellows or organ. The ‘life’ of the puppet is discerned through the rhythmic breathing motions of the puppeteer. Here the aural is conveyed through movement, rather than through sound itself, which is further a reminder that sound is at its core a movement anyway, a vibration. What can be opened up if we are to think the oral/aural through the puppet in its relation to movement and stillness, life and death?